Comparative efficacy of Bruton tyrosine kinase inhibitors in high-risk relapsed/refractory CLL: a network meta-analysis - Mazyar Shadman; Jennifer R. Brown; Leyla Mohseninejad; Keri Yang; Heather Burnett; Binod Neupane; Rhys Williams; Nicole Lamanna; Susan M. O'Brien; Alessandra Tedeschi; Constantine S. Tam (Blood Advances)
Abstract: Bruton tyrosine kinase inhibitors (BTKis) have led to changes in the treatment algorithm for patients with high-risk relapsed/refractory (R/R) chronic lymphocytic leukemia (CLL), defined based on the presence of genetic mutations. Given the lack of head-to-head trials comparing next-generation BTKis used to treat high-risk R/R disease, a network meta-analysis (NMA) was performed to estimate their relative efficacy. High-risk populations were defined based on the prespecified definitions within each trial, including patients with del(17p) and/or TP53 mutations in the ALPINE (n = 150) and ASCEND (n = 86) trials, and del(17p)/del(11q) in the ELEVATE-RR (n = 533) trial. Bayesian NMAs found zanubrutinib to be the most efficacious treatment for high-risk patients, with significantly reduced risk of progression or death compared with ibrutinib (hazard ratio [HR], 0.49; 95% credible interval [CrI], 0.31-0.78), acalabrutinib (HR, 0.55; 95% CrI, 0.32-0.94), and bendamustine + rituximab or idelalisib + rituximab (BR/IR; HR, 0.12; 95% CrI, 0.05-0.26). Differences in overall survival demonstrated a numerical trend favoring zanubrutinib (probability better than ≥80%) compared with ibrutinib (HR, 0.59; 95% CrI, 0.31-1.11), acalabrutinib (HR, 0.72; 95% CrI, 0.35-1.50), and BR/IR (HR, 0.65; 95% CrI, 0.23-1.75). Rates of response also demonstrated trends favoring zanubrutinib compared with acalabrutinib, with significant results compared with ibrutinib. The NMA suggests that the most efficacious BTKi for patients with high-risk R/R CLL is zanubrutinib.